Novel variant in HPS3 gene in a patient with Hermansky Pudlak syndrome (HPS) type 3. (2nd October 2020) - Lecchi, Anna; La Marca, Silvia; Femia, Eti A; Lenz, Antonia; Boeckelmann, Doris; Artoni, Andrea; Peyvandi, Flora; Zieger, Barbara
Abstract: Hermansky-Pudlak syndrome (HPS) is a rare autosomal recessive disorder caused by defects in 10 human HPS genes, characterized by oculocutaneous albinism (OCA) and bleeding diathesis associated to platelet δ-storage pool defect (SPD). We report a case of 4-year-old boy from non-consanguineous parents with OCA and negative personal and familiar hemorrhagic history, referred to us for severe bleeding after mild trauma. His platelet function, studied by lumi-aggregometry, showed normal first wave of aggregation in response to exogenous agonists and impaired second wave with defective ATP release. This, in combination with impaired platelet δ-granules content (serotonin, ATP, ADP) and the OCA phenotype suggested the HPS diagnosis. HPS3: sequencing revealed a novel pathogenic homozygous variant (NM_032383.4:c.7>T, p.Gln3*) resulting in a premature stop codon at the amino acid 3. Moreover, our report highlights the importance of evaluating platelet function in children with OCA without bleeding diathesis to identify HPS early and prevent bleeding complications.